Building socioeconomic resilience through an organizational culture approach: Lesson learned from the COVID-19 pandemic - Iwan Nugroho (Journal of Socioeconomics and Development, 2024)
Economic crises or shocks have become commonly encountered phenomena due to the competitive business environment and regional strategic changes.Â This situation requires business organizations and economic entities to strengthen their internal systems and organizational culture to demonstrate resilience, enabling them to survive and take recovery actions promptly. The COVID-19 pandemic demonstrates the collaboration between government, society, and economic actors to save lives, prevent the spread of the virus, and promote economic activity. This article explains how to build socioeconomic resilience through an organizational culture approach. Organizational resilience is built through long processes and time; and succeeds through challenges and adversity, so that the organization performs sustainability and resilience. Organizational resilience is significantly influenced by foresight, a flexible culture, networking, and the involvement of human resources in driving innovation.Â Essential points reviewed include the role of human resource competency, leadership, social capital, and related issues of diversity, equity, and inclusion (DEI). These points demonstrate how organizational culture enhances human-centered activities at all stages of the organization's developmentJEL ClassificationÂ H12; M14; O20To cite this article:Â Nugroho, I.Â (2024).Â Building socioeconomic resilience through an organizational culture approach: Lesson learned from the COVID-19 pandemic. Journal of Socioeconomics and Development, 7(1), v-x. https://doi.org/10.31328/jsed.v7i1.5689